Improvising Cinema - Mouëllic, Gilles (Film Culture in Transition, 2014)
This spirited volume explores the history and diversity of improvisation in the cinema, including works by Jean Renoir, Jean-Luc Godard, and Nobuhiro Suwa. Gilles Mouëllic examines improvisational practices that can be specifically attributed to the cinema and argues in favors of their powers as instigators of unprecedented forms of expression. Improvising Cinema reflects both on the permanence of attempting improvisation and the relationship between technology and aesthetics. Mouëllic concludes preservation becomes even more invaluable in the case of improvisation, as the creative act exists only within the brief time span of the performance.